Variant PTA Terminating in Cerebellar Artery, Associated with Multiple Aneurysms - Yeong Uk Hwang; Jin Woo Kim (Case Reports in Radiology)
Persistent trigeminal artery (PTA) is one of the remnant fetal anastomoses between the carotid artery and basilar artery. PTAs are classified according to angiographic appearance and various connection. Among them, those directly terminating in the cerebellar arteries are rare subtype. In addition, aneurysms of the PTA are unusual in the literature and have not previously accompanied this subtype of PTA connecting cerebellar artery. We present the first case of an aneurysm of the PTA which is directly terminating in the cerebellar arteries and combined with multiple aneurysms.